Analysis Of Raw Material Inventory Control For Production At Pentol Bakso Bapak Rizki Business In Panorama Market Bengkulu City - Fadila, Mawar; Herlin, Herlin; Harwini, Dewi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This research was conducted with the primary objective of analyzing and evaluating the existing raw material inventory control policy at Pentol Bakso Bapak Rizki Business, and subsequently formulating an optimal inventory policy to minimize total costs. The study employed a descriptive quantitative approach through a case study methodology. Data concerning ordering costs, carrying costs, and annual raw material usage were collected via interviews and documentation, then quantitatively analyzed by applying the Economic Order Quantity (EOQ), Safety Stock (SS), and Re Order Point (ROP) methods to measure the efficiency of the current policy against the recommended optimal policy. The analysis results indicate that the inventory policy currently implemented by the business, with an ordering frequency of 48 times per year, incurs a total annual inventory cost of Rp 26,140,042. Based on the EOQ calculation, the optimal order quantity is determined to be 147 kg per order, with a significantly reduced recommended ordering frequency of 6 times per year. The adoption of this method successfully lowers the total inventory cost to Rp 25,233,452, yielding a potential cost saving of Rp 906,590 annually. Furthermore, the calculated Safety Stock of 6 kg and a Re Order Point at the 9 kg level provide robust guidelines for the business to ensure uninterrupted production flow and minimize the risk of raw material shortages.